Experiences of condom fit and feel among African-American men who have sex with men. Issue 6 (15th August 2007) - Reece, Michael; Dodge, Brian; Herbenick, Debby; Fisher, Christopher; Alexander, Andreia; Satinsky, Sonya
Abstract : Objective: To offer an empirical understanding of characteristics associated with the fit and feel of condoms among African-American men who have sex with men (MSM), a particularly high-risk group for HIV and other sexually transmitted infections (STI) in the United States. Methods: Survey data were collected from 178 adult African-American MSM attending a community event in Atlanta, Georgia. Results: Although the majority of participants reported that condoms generally fit properly and felt comfortable, a substantial number of men reported a variety of problems with the fit and feel of condoms. Specifically, 21% reported that condoms felt too tight, 18% reported that condoms felt too short, 10% reported that condoms felt too loose, and 7% reported that condoms felt too long. There were significant associations between men's reports of condom breakage and slippage, and their perceptions of condom fit and feel. Perceptions of condom fit and feel were also related to men's reports of seeking condoms for their size-specific properties. Conclusions: The fit and feel issues that men in this sample identified may be among those that contribute to their likelihood of using, or not using, condoms consistently and correctly. A better understanding of these factors will be beneficial to both condom manufacturers and sexual health professionals who share a common goal of increasing consistent and correct condom use and reducing the incidence of HIV and other STI among this and other communities.